Measurement of the ratio of inclusive cross sections σ(pp̄→ Z+b-quark jet)/σ(pp̄→Z+jet) at √s=1.96TeV - Abazov, V. M.; Abbott, B.; Acharya, B. S.; Adams, M.; Adams, T.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; Alves, G. A.; Ancu, L. S.; Aoki, M.; et al. (American Physical Society (APS), 2011)
The ratio of the cross section for pp̄ interactions producing a Z boson and at least one b-quark jet to the inclusive Z+jet cross section is measured using 4.2fb-1 of pp̄ collisions collected with the D0 detector at the Fermilab Tevatron collider at √s=1.96TeV. The Z→ + - candidate events with at least one b jet are discriminated from Z+charm and light jet(s) events by a novel technique that exploits the properties of the tracks associated to the jet. The measured ratio is 0.0193±0.0027 for events having a jet with transverse momentum p T>20GeV and pseudorapidity η≤2.5, which is the most precise to date and is consistent with theoretical predictions. © 2011 American Physical Society.